Contribution of influenza to acute exacerbations of chronic obstructive pulmonary disease in Kashmir, India, 2010–2012. Issue 1 (January 2015) - Koul, Parvaiz A.; Khan, Umar H.; Asad, Romana; Yousuf, Rubaya; Broor, Shobha; Lal, Renu B.; Dawood, Fatimah S.
<x xml:space="preserve">Abstract</x> We estimate the contribution of influenza to hospitalizations for acute exacerbations of chronic obstructive pulmonary disease (AECOPD) in Kashmir, India. Prospective surveillance for influenza among patients hospitalized with AECOPD was conducted at a tertiary care hospital. Patients had clinical data collected and nasal/throat swabs tested for influenza viruses. Outcomes among patients with and without influenza were compared with logistic regression adjusting for age and underlying conditions. During October 2010–September 2012, 498 patients hospitalized with AECOPD were enrolled, of whom 40 (8%) had received influenza vaccine. Forty (8%) had influenza; influenza virus detection peaked in winter (January–March). Patients with influenza were more likely to die during hospitalization (adjusted OR 3·4, CI 1·0–11·4) than those without.